A dimensão pedagógica do programa escola comunitária de gestão compartilhada: orientações para a valoração do ensino - Cerqueira, Maria Raimunda Carvalho Araújo de (2017)
The present paper aims mainly to know the pedagogical dimension given to the Shared Management Community School Program (PECGC, in portuguese) and its financial value for teaching. It is a case study and, for that, a state-funded school in the public education system of the state of Tocantins was chosen as a research field. It is based on the investigation of the legal, theoretical and practical assumptions underlying the PECGC, based on the following question: what aspects favor or hinder the use of the PECGC resources in the pedagogical dimension in the school unit studied and what contributions can be verified in the incentive of activities and projects to valorize teaching? Thus, it was attempted to verify if the school unit, in fact, makes use of the financial resources received by the PECGC for the valorization and accomplishment of the pedagogical activities. It is an applied qualitative research with some elements of a quantitative research. techniques of bibliographic review, documentary analysis and in loco observation were used. The main authors used to ground the study theoretically were: Triviños; Saviani; Gentili; Lyra-Silva; Dourado et al .; Davies; Oliveira R .; Sant Ana; Libâneo and Carvalho. Data collection was carried out through the application of questionnaires about the pedagogical dimension of the PECGE, directed to the members of the support association, teachers and management team of the researched school unit, which we defined as the subjects / participants of the research. Finally, a semi-structured interview was conducted with the person who is in charge of directing the said school unit. The study culminated in the elaboration of the educational product: the proposition of a cost sheet for the proposal of pedagogical activities and, from this, the elaboration of a textbook with orientations for the valuation of teaching, with the purpose of suggesting a discussion on financial education, from the perspective of an administration focused on the valorization of pedagogical activities.